Twin Anemia Polycythemia Sequence: Knowledge and Insights After 15 Years of Research - Lisanne S.A. Tollenaar; Enrico Lopriore; Dick Oepkes; Monique C. Haak; Frans J.C.M. Klumper; Johanna M. Middeldorp; Jeanine M.M. Van Klink; Femke Slaghekke; Yang Pan (Wolters Kluwer Health, 2021)
Abstract. Twin anemia polycythemia sequence (TAPS) is a chronic form of unbalanced feto-fetal transfusion through minuscule placental anastomoses in monochorionic twin pregnancies, leading to anemia in the donor twin and polycythemia in the recipient twin. TAPS can occur spontaneously in up to 5% of monochorionic twins or can arise in 2%-16% of cases after incomplete laser surgery for twin-twin transfusion syndrome. TAPS can develop across the entire second and third trimester. Antenatal diagnosis for TAPS is reached via Doppler measurement of the fetal middle cerebral artery peak systolic velocity, showing an increased velocity in the donor, combined with a decreased velocity in the recipient. Treatment options for TAPS include expectant management, preterm delivery, intrauterine blood transfusion with or without a partial exchange transfusion, fetoscopic laser surgery and selective feticide. The best treatment option is unclear and is currently being investigated in an international multicenter randomized trial (the TAPS trial). Spontaneous fetal demise occurs in 5%-11% of TAPS twins, more often in donors (8%-18%) than in recipients (2%-5%). Severe long-term neurodevelopmental impairment is seen in 9% of TAPS twins, with donors having an increased risk for cognitive impairment and hearing problems (15%).